Aesthetic Evaluation in Oncoplastic and Conservative Breast Surgery: A Comparative Analysis. Issue 3 (March 2015) - Massa, Michela; Meszaros, Paolo; Baldelli, Ilaria; Bisso, Nadia; Franchelli, Simonetta
Abstract : Background: In conservative breast surgery, the achievement of a satisfactory cosmetic result could be challenging; oncoplastic techniques may be helpful in many cases. A comparative analysis was performed among 3 groups of patients undergoing oncoplastic techniques plus external radiation therapy or intraoperative radiotherapy (IORT) and breast conservative surgery plus external radiation therapy; long-term oncologic results in terms of disease relapse and aesthetic outcomes were compared. Methods: Ninety-six patients were considered: 32 patients treated with oncoplastic surgery, 16 then subjected to radiotherapy (group 1) and another 16 treated with IORT (group 2); 64 patients treated by conservative surgery and radiotherapy formed the control group (group 3). Patients were asked to give a judgment on the cosmetic result considering the following parameters: breast symmetry, appearance of the residual scar, symmetry between the 2 nipple-areola complexes, global aesthetic judgment, and satisfaction about the result. Results: With respect to the oncological and aesthetic outcome, the statistical significance of the results obtained in the 3 groups was calculated using the chi-square test. The results, processed by the chi-square test, were not statistically significant; however, the overall judgments expressed by the patients of all 3 groups were more than satisfactory (scores greater than or equal to 6). Conclusions: In our experience, when the inclusion criteria are satisfied and the equipment is available, oncoplastic techniques associated with IORT should be considered the treatment of choice for breast cancer in early stage. The excellent cosmetic results and patient's satisfaction encourage us to continue on this way.